Công văn của Thủ tướng Chính phủ về việc trả lời chất vấn của Đại biểu Quốc hội (Số: 1960/TTg-QHĐP) - Thủ tướng Chính phủ (2017)
Công văn của Thủ tướng Chính phủ về việc trả lời chất vấn của Đại biểu Quốc hội (Số: 1960/TTg-QHĐP) ngày 20/12/2017